2020
DOI: 10.1111/tbed.13644
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence and subtypes of Blastocystis sp. in primates in northern China

Abstract: Blastocystis sp. is the most common gastrointestinal eukaryotic parasite in humans; it is also common in many animals worldwide (Alfellani et al., 2013; Hazhir, Shahram, Shahrzad, Mehdi, & Elham, 2014). As a pathogen of zoonosis, Blastocystis sp. has been found in Primates, Rodentia, Artiodactyla, Perissodactyla and Aves. However, there is a dispute regarding the pathogenicity of Blastocystis sp., since the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
2
23
2
Order By: Relevance
“…Interestingly, a more recent study showed zoo animals and staff were infected with ST1-3 and showed high consistency with known sequences from NHPs and humans, highlighting that these STs have zoonotic potential [ 38 ]. In China, ST1, ST2, ST3, ST4, ST5, ST9, ST10, and ST13 were identified in NHPs [ 27 , 31 , 39 , 40 ], with ST1 and ST2 being the most common. In this study, Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a more recent study showed zoo animals and staff were infected with ST1-3 and showed high consistency with known sequences from NHPs and humans, highlighting that these STs have zoonotic potential [ 38 ]. In China, ST1, ST2, ST3, ST4, ST5, ST9, ST10, and ST13 were identified in NHPs [ 27 , 31 , 39 , 40 ], with ST1 and ST2 being the most common. In this study, Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…ST1, ST2, ST3, ST4, ST5, ST6 and ST7 were found common to humans and animals. ST9 was observed in ring-tailed lemurs and chickens in China [250] and Malaysia [15] respectively; however, no article included in this review reported on the identification of ST9 in humans in these countries. The characteristic presence of ST5 in pigs, ST10 and ST14 in goats, sheep and cattle, and ST6 and ST7 in chickens underscore suggestions that these STs are specific to the respective animal hosts.…”
Section: Discussionmentioning
confidence: 99%
“…ST5 is commonly isolated from livestock, ST6 and ST7 from birds, and ST8 from arboreal non-human primates [ 15 , 16 , 17 ]). In addition to humans, ST9 has been recently described in poultry and non-human primates [ 18 , 19 ]. The fact that ST5‒ST8, ST10, ST12, and ST14 have been only sporadically found in humans has been interpreted as indicative of zoonotic activity [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%